2015
DOI: 10.1088/0953-8984/27/19/194104
|View full text |Cite
|
Sign up to set email alerts
|

Transverse excitations in liquid Fe, Cu and Zn

Abstract: Transverse acoustic (TA) excitation modes were observed in inelastic x-ray scattering spectra of liquid Fe, Cu and Zn. From the analysis of current correlation functions, we concluded that TA excitation modes can experimentally be detected through the quasi-TA branches in the longitudinal current correlation spectra in these liquid metals. The microscopic elastic constants are estimated and a characteristic difference from macroscopic polycrystalline value was found in Poisson's ratio of liquid Fe, which shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 30 publications
8
95
0
Order By: Relevance
“…This prompted the experimentalists to suggest the existence of a second propagating mode of energy lying within this region, and showed that a t based on two propagating modes produces better results than a t based on just one of them. Specically, they used a Lorentzian function to account for the central peak and a damped harmonic oscilator (DHO) for each of the propagating modes [4]. The variation with q of the frequencies of the modes obtained from the ts leads to a dispersion relation (DR) with two branches, a high frequency one that displays a positive dispersion with respect to the hydrodynamic sound velocity, and that is similar to the usual DR in liquid systems, plus a lower energy branch, which has been interpreted as a ngerprint of tranverse waves in the dynamics of density uctuations.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…This prompted the experimentalists to suggest the existence of a second propagating mode of energy lying within this region, and showed that a t based on two propagating modes produces better results than a t based on just one of them. Specically, they used a Lorentzian function to account for the central peak and a damped harmonic oscilator (DHO) for each of the propagating modes [4]. The variation with q of the frequencies of the modes obtained from the ts leads to a dispersion relation (DR) with two branches, a high frequency one that displays a positive dispersion with respect to the hydrodynamic sound velocity, and that is similar to the usual DR in liquid systems, plus a lower energy branch, which has been interpreted as a ngerprint of tranverse waves in the dynamics of density uctuations.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…The variation with q of the frequencies of the modes obtained from the ts leads to a dispersion relation (DR) with two branches, a high frequency one that displays a positive dispersion with respect to the hydrodynamic sound velocity, and that is similar to the usual DR in liquid systems, plus a lower energy branch, which has been interpreted as a ngerprint of tranverse waves in the dynamics of density uctuations. The existence of these two modes was rst suggested for liquid Ga and later also for other liquid metals (Sn, Fe, Cu, Na) [4,13], based on the similarity between the frequencies observed and those of transverse excitations either in the corresponding solid or in the liquid. However, at present no theoretical approach has been able to explain their appearance.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
See 3 more Smart Citations